A method for preparing a negative electrode friction material for a friction nanogenerator, a friction nanogenerator and its application

The aluminum template is prepared by spraying edible salt powder and scraping polydimethylsiloxane to form a negative electrode friction material with a micro-nano structure, which solves the problem of poor power supply capacity of existing friction nanogenerators, and achieves more efficient electrical output performance and wider application prospects.

CN115912984BActive Publication Date: 2025-04-15INST OF OCEANOLOGY - CHINESE ACAD OF SCI +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211250702.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-12
Publication Date
2025-04-15
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

The negative friction material of existing friction nanogenerators has a smooth surface and a small effective friction area, resulting in poor power supply capacity and limited application.

Method used

The aluminum template is prepared by spraying edible salt powder onto the aluminum plate and scraping the polydimethylsiloxane onto the aluminum template to form a negative electrode friction material with a micro-nano structure.

Benefits of technology

It improves the electrical output performance of friction nanogenerators, increases the effective contact area, and improves the power supply capacity. It is suitable for commercial electronic equipment power supply and metal corrosion protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115912984B_ABST
    Figure CN115912984B_ABST
Patent Text Reader

Abstract

The present invention proposes a method for preparing a negative electrode friction material for a friction nanogenerator, a friction nanogenerator and an application. The present invention comprises the following steps: 1) taking commercial edible salt, grinding, screening, and obtaining edible salt powder; 2) spraying the edible salt powder onto an aluminum plate, ultrasonicating, and obtaining an aluminum template; 3) taking a prepolymer and a curing agent, mixing them evenly, standing for 30-40 minutes under a vacuum state, and obtaining polydimethylsiloxane; 4) applying polydimethylsiloxane to an aluminum template by scraping, vacuum drying for 2.0-2.5 hours at 50-65°C, and peeling off to obtain a negative electrode friction material for a friction nanogenerator. The template surface of the present invention has many and fine pits, the obtained negative electrode friction material has a large surface roughness, a simple process, low cost, can be prepared on a large area, the template can be repeatedly used, and is economical and practical; the obtained friction nanogenerator has a good power supply capacity, a good application prospect, and can be used for corrosion protection of metals with a good anti-corrosion effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of friction generators, and in particular to a method for preparing a negative electrode friction material for a friction nanogenerator, a friction nanogenerator and applications thereof. Background Art

[0002] Corrosion is a failure and destruction phenomenon that all materials in nature have to face. It has caused huge losses to human society, such as resource consumption, environmental pollution and industrial accidents, endangering human health and safety, and causing huge economic losses. According to relevant statistics, corrosion losses account for about 3-5% of the gross domestic product (GDP) of each country each year, and the metal equipment and materials scrapped each year due to corrosion account for about 10-40% of the annual output of metals. In electrochemical corrosion protection technology, the impressed current method requires an external power supply, and energy supply needs to be improved. In 2012, scientific and technological workers first proposed a friction nanogenerator based on the coupling of triboelectric effect and electrostatic induction effect. This friction nanogenerator has four basic working modes and can collect different forms of energy, including human movement, vibration, tire rotation, wind energy, water energy, etc. The friction nanogenerator has the advantages of light weight, low cost, diverse structure, wide selection of materials, and even extremely high efficiency at low operating frequencies. Many technicians combine the friction nanogenerator with the impressed current cathodic protection method to achieve the protection of the metal cathode and complete the collection and self-utilization of energy.

[0003] The friction nanogenerator is mainly composed of a first electrode, a first friction material, a second friction material and a second electrode. The first electrode and the first friction material form a negative electrode. The first electrode is usually made of copper. The first friction material is also called a negative electrode friction material, usually a polydimethylsiloxane film. The second friction material and the second electrode form a positive electrode. The second friction material is also called a positive electrode friction material. The positive electrode friction material is usually made of aluminum. Aluminum itself can conduct electricity and it is also an electrode. Aluminum can be directly used in the positive electrode. The existing polydimethylsiloxane film negative electrode friction material has a smooth surface and a small effective friction area. The power supply capacity of the friction nanogenerator obtained from it is poor, which limits its application. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a negative electrode friction material for a friction nanogenerator, a friction nanogenerator and its application, aiming to solve the problem that the polydimethylsiloxane film used as the negative electrode friction material of the friction nanogenerator in the prior art has a smooth surface and a small effective friction area, resulting in poor power supply capacity of the resulting friction nanogenerator and limited application.

[0005] In order to solve the above technical problems, the technical solution of the present invention is achieved as follows:

[0006] In one aspect, a method for preparing a negative electrode friction material for a friction nanogenerator of the present invention comprises the following steps: 1) taking commercial edible salt, grinding, and sieving to obtain edible salt powder; 2) taking an aluminum plate, spraying the edible salt powder obtained in step 1) onto the aluminum plate, with a spraying pressure of 5-7 KPa, a spraying time of 3-4 min, and ultrasonication for 20-30 min to obtain an aluminum template; 3) taking a prepolymer and a curing agent, with a weight ratio of the prepolymer to the curing agent of 10-12:1, mixing them evenly, and standing for 30-40 min under vacuum to obtain polydimethylsiloxane; 4) scraping the polydimethylsiloxane obtained in step 3) onto the aluminum template obtained in step 2) to obtain a polydimethylsiloxane film with a thickness of 450-650 μm, vacuum drying at 50-65°C for 2.0-2.5 h, and peeling off to obtain a negative electrode friction material for a friction nanogenerator with a micro-nano structure on one side.

[0007] The present invention sprays edible salt powder onto an aluminum plate to prepare an aluminum template. The surface of the aluminum template has many fine pits, and the surface roughness of the negative electrode friction material for the friction nanogenerator obtained therefrom is large. Moreover, the aluminum template can be used repeatedly and is highly practical. The preparation method of the negative electrode friction material for the friction nanogenerator has a simple process, low cost, can be prepared on a large area, and is easy to realize industrialization. When the friction nanogenerator is used to supply power for commercial electronic equipment, it shows good power supply capacity and has good application prospects. Moreover, when the cathode protection technology coupled with the friction nanogenerator is applied to the corrosion protection of metals, the potential of the metal cathode is greatly reduced to below the self-corrosion potential, which effectively slows down or inhibits metal corrosion, and has great application potential in self-powered anti-corrosion.

[0008] In the present invention, the polydimethylsiloxane may be SYLGARD 184, wherein the prepolymer is SYLGARD 184 Silicone Elastomer Base, and the curing agent is SYLGARD 184 Silicone Elastomer Curing. The basic principle of the present invention is to improve the electrical output performance of the friction nanogenerator by modifying the surface of the friction material, that is, constructing a special micro-nano structure on the surface of the polydimethylsiloxane, which is attributed to the increase in the effective contact area, which not only increases the number of positions that can generate electric charges, but also enhances the position capture capability by modifying the morphology of the friction material surface.

[0009] As a preferred embodiment, in the step 2), the edible salt powder is sprayed onto the aluminum template using a pneumatic self-priming sandblasting gun, the distance between the gun head of the pneumatic self-priming sandblasting gun and the aluminum plate is 10-20 cm, and the angle between the gun head and the aluminum plate is 0-45 degrees. This pneumatic self-priming sandblasting gun is easy to use and has a good spraying effect. One port of the pneumatic self-priming sandblasting gun is connected to the edible salt powder, and the other port is connected to the air compressor. The distance and fixed angle between the gun head and the aluminum plate are kept small, and the edible salt powder is sprayed on the aluminum plate, and the spraying is repeated to obtain an aluminum plate with edible salt powder evenly attached to the surface.

[0010] As a preferred embodiment, in step 2), the ultrasonic treatment is performed using deionized water, and the deionized water is replaced every 3-5 minutes. In the present invention, the aluminum plate with edible salt powder uniformly attached to the surface is treated with deionized water ultrasonic treatment to obtain a clean aluminum template.

[0011] As a preferred embodiment, in the step 4), the thickness of the polydimethylsiloxane film is 500-600 μm. The present invention adopts a scraping method, usually an automatic scraping instrument, to scrape the friction material (polydimethylsiloxane) on the aluminum template, and after curing, the micro-nano structure of the aluminum template is copied to the surface of the polydimethylsiloxane film, thereby obtaining a polydimethylsiloxane film with a micro-nano structure on the surface, which is used as a friction material for making a friction nanogenerator.

[0012] As a preferred embodiment, in the step 1), the particle size of the edible salt powder does not exceed 10 μm. The present invention controls the particle size of the edible salt powder. The smaller the particle size of the edible salt powder, the more and denser the pits of the obtained aluminum template, and the greater the surface roughness of the negative electrode friction material for the triboelectric nanogenerator obtained therefrom.

[0013] As a preferred embodiment, in the step 1), the grinding time is 3-5 minutes. The present invention uses commercial edible salt, which is widely available, low in price and easy to obtain. Usually, a pulverizer is used to grind the edible salt to obtain edible salt powder.

[0014] As a preferred embodiment, in the step 3), the standing is completed at room temperature. After the prepolymer and the curing agent of the present invention are evenly mixed, they are placed in a vacuum at room temperature to remove bubbles in the mixture, and the polydimethylsiloxane after the bubbles are removed can be evenly scraped on the aluminum template.

[0015] In another aspect, the present invention provides a negative electrode friction material for a friction nanogenerator, wherein the negative electrode friction material for a friction nanogenerator is prepared according to any one of the above methods for preparing a negative electrode friction material for a friction nanogenerator.

[0016] The present invention constructs a micro-nano structure on the surface of the negative electrode friction material used in the friction nanogenerator, thereby improving the surface roughness of the negative electrode friction material. The surface friction of the negative electrode friction material is greater, which increases the effective contact area between the friction materials, thereby improving the electrical output performance of the friction nanogenerator and achieving good use effect.

[0017] In another aspect, a friction nanogenerator of the present invention comprises a stacked negative electrode, a negative electrode friction material and a positive electrode, wherein the negative electrode friction material is the negative electrode friction material for the friction nanogenerator described above, and the side of the negative electrode friction material having the micro-nano structure faces the positive electrode.

[0018] The surface roughness of the negative electrode friction material for the friction nanogenerator of the present invention is large, and the surface friction between the negative electrode friction material and the positive electrode is greater. The electrical output performance of the friction nanogenerator obtained therefrom is significantly improved. When the friction nanogenerator is used as a power source and is applied to power different commercial electronic devices, it shows good power supply capacity and has good application prospects. The negative electrode friction material of the present invention is polydimethylsiloxane, and the electrode material attached to the back is copper. The positive electrode friction material is aluminum, which can conduct electricity itself and is also an electrode.

[0019] In yet another aspect, the present invention provides an application of a friction nanogenerator, wherein the friction nanogenerator is used for metal corrosion protection.

[0020] When the friction nanogenerator of the present invention is applied to cathodic protection, the friction nanogenerator is used as a power source, coupled with cathodic protection technology, and applied to the field of metal corrosion and protection, which effectively slows down or inhibits metal corrosion. It has great application potential in self-powered anti-corrosion, and greatly reduces the potential of 304 stainless steel to below the self-corrosion potential.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention sprays edible salt powder onto an aluminum plate to prepare an aluminum template, the surface of the aluminum template has many fine pits, the surface roughness of the negative electrode friction material for the friction nanogenerator obtained therefrom is large, and the aluminum template can be reused and is highly practical. The preparation method of the negative electrode friction material for the friction nanogenerator has a simple process, low cost, can be prepared on a large area, and is easy to industrialize; when the friction nanogenerator is used to power commercial electronic equipment, it exhibits good power supply capacity and has good application prospects; and when the cathodic protection technology coupled with the friction nanogenerator is applied to metal corrosion protection, the potential of the metal cathode is greatly reduced to below the self-corrosion potential, effectively slowing down or inhibiting metal corrosion, and has great application potential in self-powered anti-corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1This is a digital photo of the aluminum template obtained in Example 1 of the method for preparing a negative electrode friction material for a triboelectric nanogenerator provided by the present invention;

[0023] Figure 2 for Figure 1 Scanning electron microscope photo of the Chalco template;

[0024] Figure 3 This is a scanning electron microscope photograph of the negative electrode friction material for the triboelectric nanogenerator obtained in Example 1;

[0025] Figure 4 for Figure 3 Enlarged view of the circled part;

[0026] Figure 5 This is a diagram showing the short-circuit current test results of the friction nanogenerator obtained in Example 1;

[0027] Figure 6 This is a graph showing the open circuit voltage test results of the friction nanogenerator obtained in Example 1;

[0028] Figure 7 This is a graph showing the test results of the surface charge density of the triboelectric nanogenerator obtained in Example 1;

[0029] Figure 8 The friction nanogenerator obtained in Example 1 is a charging curve diagram of capacitors with different capacities;

[0030] Fig. 9 This is a curve diagram of the triboelectric nanogenerator obtained in Example 1 supplying power to a calculator;

[0031] Fig.10 This is a charging curve diagram of a small watch using the friction nanogenerator obtained in Example 1;

[0032] Fig.11 This is a curve diagram of the friction nanogenerator obtained in Example 1 supplying power to an LED bulb;

[0033] Fig.12 This is a test diagram of the corrosion protection effect of the friction nanogenerator obtained in Example 1 on metal;

[0034] Fig.13 This is a digital photo of the aluminum template obtained in Comparative Example 1;

[0035] Fig.14 for Fig.13 Scanning electron microscope photo of the Chalco template;

[0036] Fig.15 This is a scanning electron microscope photograph of the negative electrode friction material for the triboelectric nanogenerator obtained in Comparative Example 1;

[0037] Fig.16 The charging curve of the friction nanogenerator obtained in comparative example 1 for capacitors with different capacities;

[0038] In the figure: A——SP-TENG; B——RP-TENG;

[0039] 1——100μF; 2——47μF; 3——33μF; 4——22μF; 5——10μF; 6——4.7μF; 7——3.3μF; 8——2.2μF; 9——1μF. DETAILED DESCRIPTION

[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] A method for preparing a negative electrode friction material for a triboelectric nanogenerator of the present invention comprises the following steps:

[0042] 1) Take commercial edible salt, grind it, and sieve it to obtain edible salt powder;

[0043] 2) Take an aluminum plate, spray the edible salt powder obtained in step 1) onto the aluminum plate, the spraying pressure is 5-7 KPa, the spraying time is 3-4 min, and the ultrasonic treatment is performed for 20-30 min to obtain an aluminum template;

[0044] 3) taking a prepolymer and a curing agent, wherein the weight ratio of the prepolymer to the curing agent is 10-12:1, mixing them evenly, and standing them for 30-40 minutes under a vacuum state to obtain polydimethylsiloxane;

[0045] 4) The polydimethylsiloxane obtained in step 3) is scraped onto the aluminum template obtained in step 2) to obtain a polydimethylsiloxane film with a thickness of 450-650 μm, which is vacuum dried at 50-65° C. for 2.0-2.5 hours and peeled off to obtain a negative electrode friction material for a friction nanogenerator with a micro-nano structure on one side.

[0046] Preferably, in step 2), the edible salt powder is sprayed onto the aluminum template using a pneumatic self-priming sandblasting gun, the distance between the gun head of the pneumatic self-priming sandblasting gun and the aluminum plate is 10-20 cm, and the angle between the gun head and the aluminum plate is 0-45 degrees.

[0047] Preferably, in step 2), the ultrasound is carried out using deionized water, and the deionized water is replaced every 3-5 minutes.

[0048] Preferably, in step 4), the thickness of the polydimethylsiloxane film is 500-600 μm.

[0049] Preferably, in step 1), the particle size of the edible salt powder does not exceed 10 μm.

[0050] Preferably, in step 1), the grinding time is 3-5 min.

[0051] Preferably, in step 3), the standing is performed at room temperature.

[0052] The present invention provides a negative electrode friction material for a friction nanogenerator, wherein the negative electrode friction material for a friction nanogenerator is prepared according to any one of the above methods for preparing a negative electrode friction material for a friction nanogenerator.

[0053] A friction nanogenerator of the present invention comprises a stacked negative electrode, a negative electrode friction material and a positive electrode. The negative electrode friction material is the negative electrode friction material for the friction nanogenerator described above, and the side of the negative electrode friction material having the micro-nano structure faces the positive electrode.

[0054] The invention discloses an application of a friction nanogenerator, wherein the friction nanogenerator is used for metal corrosion protection.

[0055] Embodiment 1

[0056] (I) Preparation of negative electrode friction materials for triboelectric nanogenerators

[0057] A method for preparing a negative electrode friction material for a triboelectric nanogenerator of the present invention comprises the following steps:

[0058] 1) Take commercial edible salt, grind it with a grinder for 3 minutes, and sieve it to obtain edible salt powder with a particle size of 10 μm;

[0059] 2) Take an aluminum plate of size 50×50×1 mm, and use a pneumatic self-priming sandblasting gun to spray the edible salt powder obtained in step 1) onto the aluminum plate, one port of the pneumatic self-priming sandblasting gun is connected to the edible salt powder, and the other port is connected to an air compressor, the spraying pressure of the air compressor is 6 KPa, the distance between the gun head of the pneumatic self-priming sandblasting gun and the aluminum plate is 15 cm, and the angle between the gun head and the aluminum plate is 30 degrees, and the edible salt powder is sprayed on the aluminum plate, and the spraying is repeated for 3 minutes to obtain an aluminum plate with edible salt powder evenly attached to the surface, and the aluminum plate with edible salt powder evenly attached to the surface is ultrasonically treated with deionized water for 25 minutes, and the deionized water is replaced once every 5 minutes to obtain a clean aluminum template;

[0060] 3) taking a prepolymer and a curing agent in a weight ratio of 10:1, mixing them evenly, standing them at room temperature in a vacuum for 30 minutes, removing bubbles in the mixture, and obtaining polydimethylsiloxane;

[0061] 4) Using an automatic scraping instrument, the polydimethylsiloxane obtained in step 3) is scraped onto the aluminum template obtained in step 2) to obtain a polydimethylsiloxane film with a thickness of 500 μm, which is then transferred to a vacuum drying oven and vacuum dried at 60°C for 2.0 h. It is manually peeled off from the aluminum film plate to obtain a negative electrode friction material for a friction nanogenerator with a micro-nano structure on one side.

[0062] (II) Performance test

[0063] The aluminum template obtained in step 2) is photographed with a digital camera. Figure 1 It can be seen that the surface of the aluminum template obtained in the present invention is rough and white. This is because the construction of the surface micro-nano structure causes the direction of light to be lost and deviated when passing through the rough surface.

[0064] The aluminum template obtained in step 2) was placed on a Nova NanoSem450 scanning electron microscope produced by FEI Company of the United States for observation. Figure 2 It can be seen that after ultrasonic treatment, the edible salt particles of the aluminum template of the present invention are detached and dissolved very cleanly, no edible salt particles are attached, and the entire plane is full of protrusions and pits, which shows that the present invention has well constructed a micro-nano structure on the surface of the aluminum template.

[0065] The negative electrode friction material for the triboelectric nanogenerator with micro-nano structure on one side obtained in this embodiment was placed on the above-mentioned scanning electron display mirror for observation. Figure 3 and attached Figure 4 It can be seen that the surface of the negative electrode friction material for the friction nanogenerator obtained by the present invention is full of wrinkles, which shows that polydimethylsiloxane has good fluidity under vacuum and perfectly replicates the morphology of the aluminum template.

[0066] Comparative Example 1

[0067] (I) Preparation of negative electrode friction materials for triboelectric nanogenerators

[0068] A negative electrode friction material for a friction nanogenerator comprises the following steps:

[0069] 1) Take an aluminum plate of 50×50×1 mm in size, and use deionized water for ultrasonic treatment for 25 min, replacing the deionized water every 5 min to obtain a clean aluminum template;

[0070] 2) taking a prepolymer and a curing agent in a weight ratio of 10:1, mixing them evenly, standing them at room temperature in a vacuum for 30 minutes, removing bubbles in the mixture, and obtaining polydimethylsiloxane;

[0071] 3) Using an automatic scraping instrument, the polydimethylsiloxane obtained in step 2) is scraped onto the aluminum template obtained in step 1) to obtain a polydimethylsiloxane film with a thickness of 500 μm, which is then transferred to a vacuum drying oven and vacuum dried at 60° C. for 2.5 h. It is manually peeled off from the aluminum film plate to obtain a negative electrode friction material for a friction nanogenerator.

[0072] (II) Performance test

[0073] The aluminum plate obtained in step 1) was photographed with a digital camera. Fig.13 It can be seen that the surface of the untreated aluminum template is smooth and silvery white.

[0074] The aluminum template obtained in step 1) was placed on a Nova NanoSem450 scanning electron microscope produced by FEI Company of the United States for observation. Fig.14 It can be seen that the surface of the untreated aluminum template is flat and smooth.

[0075] The negative electrode friction material for the triboelectric nanogenerator obtained in this comparative example 1 was placed on the above-mentioned scanning electron display mirror for observation. Fig.15 It can be seen that the surface of the negative electrode friction material used in this friction nanogenerator is smooth and flat.

[0076] Experiment 1

[0077] The aluminum template obtained in Example 1 and the aluminum template obtained in Comparative Example 1 were respectively placed on a vk-x250 laser confocal microscope produced by Japan KEYENCE Company to measure their CLSM roughness.

[0078] The experimental results are listed in Table 1.

[0079] Sample name <![CDATA[S q (μm)]]> <![CDATA[S a (μm)]]> Embodiment 1 2.065 1.604 Comparative Example 1 0.382 0.308

[0080] It can be seen from Table 1 that the surface roughness of the aluminum template obtained by the present invention is 5.4 times higher than that of the aluminum film plate of Comparative Example 1 in terms of root mean square height Sq and 5.2 times higher in terms of arithmetic mean height Sa; therefore, the surface of the aluminum template of the present invention has a better micro-nano structure.

[0081] The negative electrode friction material for the triboelectric nanogenerator obtained in Example 1 and the negative electrode friction material for the triboelectric nanogenerator obtained in Comparative Example 1 were placed on a vk-x250 laser confocal microscope produced by KEYENCE, Japan, to measure their CLSM roughness. The experimental results are listed in Table 2.

[0082] Sample name <![CDATA[S q (μm)]]> <![CDATA[S a (μm)]]> Embodiment 1 1.167 1.278 Comparative Example 1 0.310 0.241

[0083] It can be seen from Table 2 that the surface roughness of the negative electrode friction material for the friction nanogenerator obtained by the present invention is 3.7 times higher than that of the surface roughness of the negative electrode friction material for the friction nanogenerator in Comparative Example 1 in terms of the root mean square height Sq, and the arithmetic mean height Sa is 5.3 times higher; therefore, the polydimethylsiloxane of the present invention effectively replicates the micro-nano structure of the aluminum template surface.

[0084] Experiment 2

[0085] (I) Assembly of triboelectric nanogenerator

[0086] The negative electrode friction materials for the friction nanogenerator obtained in Example 1 and Comparative Example 1 were cut into small pieces (25mm×25mm), and pasted onto a copper tape (50mm×25mm×0.08mm). The other side of the copper tape was pasted onto two layers of foam double-sided tape (25mm×25mm×1mm); the other side of the foam double-sided tape was pasted onto the center of an acrylic plate (50mm×50mm×2mm); a wire was pasted onto one end of the copper tape and fixed to one side of the acrylic plate for transmitting electrical energy, thereby obtaining the negative electrode of the friction nanogenerator.

[0087] Take an aluminum sheet (0.2 mm thick) of the same size as the negative electrode friction material for the friction nanogenerator and follow the same steps to obtain the positive electrode of the friction nanogenerator.

[0088] The above-mentioned negative electrode and positive electrode were fixed on a simple motor with the maximum gap between the two poles fixed at 11 mm, and they were assembled into a vertical contact separation friction nanogenerator (RP-TENG) and a vertical contact separation friction nanogenerator (SP-TENG), respectively.

[0089] (II) Performance test

[0090] 1. Electrical output performance

[0091] The electrical output performance of the triboelectric nanogenerators obtained in Example 1 and Comparative Example 1 was tested respectively. The triboelectric nanogenerator was driven by a simple motor (driving frequency was 10 Hz) to generate alternating current. The short-circuit current and surface charge were measured using an electrometer K6514, and the surface charge density was calculated by the surface charge and electrode area. The open-circuit voltage was tested using an oscilloscope. Figure 5 It can be seen that compared with SP-TENG, the short-circuit current of RP-TENG increases from 10μA to 26μA, an increase of 2.6 times. Figure 6It can be seen that compared with SP-TENG, the open circuit voltage of RP-TENG increases from 300 V to 600 V, which is 2 times higher. Figure 7 It can be seen that the surface charge density of SP-TENG is 60 μC / m 2 , while the surface charge density of RP-TENG is 125μC / m 2 . Therefore, the negative electrode friction material for the friction nanogenerator prepared using the aluminum template of the present invention effectively constructs the micro-nano structure of the PDMS surface, which helps to improve the electrical output performance of the friction nanogenerator. The enhanced performance of the friction nanogenerator is attributed to the increase in the roughness of the friction material. The tip and root of the PDMS surface structure gradually contact the pressure and produce continuous deformation, which increases the actual contact area between the two friction materials, thereby generating more friction charges, resulting in a relatively large output. Therefore, RP-TENG has a faster charging speed relative to SP-TENG, which is attributed to the higher short-circuit current and open-circuit voltage of RP-TENG relative to SP-TENG.

[0092] 2. Charging performance

[0093] The friction nanogenerator obtained in Example 1 was tested for charging performance. The friction nanogenerator obtained in Example 1 was driven by a simple motor (driving frequency of 10 Hz) to generate alternating current, which was converted into direct current after rectification by a rectifier bridge, and connected to different commercial electronic devices (e.g., capacitors, calculators, small watches) via wires to power them, and the changes in electrical signals were tested using an oscilloscope or K6514 electrometer. In order to more intuitively evaluate the electrical output performance of RP-TENG, RP-TENG was used to charge different electronic devices.

[0094] By the attached Figure 8 It can be seen that when RP-TENG is used to charge capacitors of 4.7μF and 47μF within 60s, the potential reaches 20.8V and 2.98V respectively; RP-TENG has a faster charging speed for charging capacitors of different capacities, which is due to the higher short-circuit current and open-circuit voltage of RP-TENG. Fig. 9 and attached Fig.10 It can be seen that by rectifying and coupling a 100μF capacitor, the RP-TENG can provide energy for the calculator and watch and enable them to work continuously. Fig.11 It can be seen that RP-TENG can also light up 270 LEDs. RP-TENG has good power supply capability and has good application prospects in powering commercial electronic devices.

[0095] The friction nanogenerator obtained in this comparative example 1 was tested for charging performance. The friction nanogenerator obtained in comparative example 1 was driven by a simple motor (driving frequency was 10HZ) to generate alternating current, which was rectified by a rectifier bridge and converted into direct current. The direct current was connected to different capacitors through wires to charge the capacitors, and the changes in the test points were tested using an electrometer K6514. Fig.16 It can be seen that when using SP-TENG, the potentials are 8.07 V and 0.848 V, respectively, which indicates that the charging speed of RP-TENG is faster than that of SP-TENG for charging capacitors of different capacities, which is due to the higher short-circuit current and open-circuit voltage of RP-TENG.

[0096] Experiment 3

[0097] The corrosion protection effect of the triboelectric nanogenerator obtained in Example 1 on metals was tested. The triboelectric nanogenerator obtained in Example 1 was driven by a simple motor (driving frequency was 10 Hz) to generate alternating current, which was converted into direct current after rectification by a rectifier bridge. A 3.5 wt% NaCl solution was contained in the corrosion electrolytic cell to simulate the seawater environment. A three-electrode system (calomel electrode as reference electrode, platinum electrode as counter electrode, 304 stainless steel as working electrode) was prepared. The current flowed from the counter electrode to the working electrode, and the flow direction of the electrons was opposite to the flow direction of the current. The electrochemical workstation was used to test the changes in the electrochemical signals of the metal before and after protection.

[0098] By the attached Fig.12 It can be seen that when 304 stainless steel is immersed in 3.5% NaCl solution, the potential is stable at about -0.21V; when the circuit is turned on, the electrons generated by the friction nanogenerator of the present invention are transferred to the surface of the 304 stainless steel, and the potential quickly drops to about -0.40V, a decrease of about 190mV; when the circuit is turned off again, the potential of the 304 stainless steel quickly recovers. This shows that the present invention effectively provides cathodic protection for the friction nanogenerator metal.

[0099] Therefore, compared with the prior art, the beneficial effects of the present invention are as follows: the present invention sprays edible salt powder onto an aluminum plate to prepare an aluminum template, the surface of the aluminum template has many fine pits, the surface roughness of the negative electrode friction material for the friction nanogenerator obtained therefrom is large, and the aluminum template can be reused and is highly practical. The preparation method of the negative electrode friction material for the friction nanogenerator has a simple process, low cost, can be prepared on a large area, and is easy to industrialize; when the friction nanogenerator is used to power commercial electronic equipment, it exhibits good power supply capacity and has good application prospects; and, when the cathodic protection technology coupled with the friction nanogenerator is applied to metal corrosion protection, the potential of the metal cathode is greatly reduced to below the self-corrosion potential, effectively slowing down or inhibiting metal corrosion, and has great application potential in self-powered anti-corrosion.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode friction material for a triboelectric nanogenerator, characterized in that: The following steps are involved: 1) Take commercial edible salt, grind it, and sieve it to obtain edible salt powder; 2) Take an aluminum plate, spray the edible salt powder obtained in step 1) onto the aluminum plate, the spraying pressure is 5-7 KPa, the spraying time is 3-4 min, and the ultrasonic treatment is performed for 20-30 min to obtain an aluminum template; 3) taking a prepolymer and a curing agent, wherein the weight ratio of the prepolymer to the curing agent is 10-12:1, mixing them evenly, and standing them for 30-40 minutes under a vacuum state to obtain polydimethylsiloxane; 4) The polydimethylsiloxane obtained in step 3) is scraped onto the aluminum template obtained in step 2) to obtain a polydimethylsiloxane film with a thickness of 450-650 μm, which is vacuum dried at 50-65° C. for 2.0-2.5 hours and peeled off to obtain a negative electrode friction material for a friction nanogenerator with a micro-nano structure on one side.

2. The method for preparing the negative electrode friction material for the triboelectric nanogenerator according to claim 1, characterized in that: In the step 2), the edible salt powder is sprayed onto the aluminum plate by a pneumatic self-priming sandblasting gun, the distance between the gun head of the pneumatic self-priming sandblasting gun and the aluminum plate is 10-20 cm, and the angle between the gun head and the aluminum plate is 0-45 degrees.

3. The method for preparing the negative electrode friction material for the triboelectric nanogenerator according to claim 2, characterized in that: In the step 2), the ultrasound is performed using deionized water, and the deionized water is replaced every 3-5 minutes.

4. The method for preparing the negative electrode friction material for the triboelectric nanogenerator according to claim 1, characterized in that: In the step 4), the thickness of the polydimethylsiloxane film is 500-600 μm.

5. The method for preparing the negative electrode friction material for the triboelectric nanogenerator according to any one of claims 1 to 4, characterized in that: In the step 1), the particle size of the edible salt powder does not exceed 10 μm.

6. The method for preparing the negative electrode friction material for the triboelectric nanogenerator according to claim 5, characterized in that: In the step 1), the grinding time is 3-5 minutes.

7. The method for preparing the negative electrode friction material for the triboelectric nanogenerator according to claim 1, characterized in that: In the step 3), the standing is performed at room temperature.

8. A negative electrode friction material for a triboelectric nanogenerator, characterized in that: The negative electrode friction material for a friction nanogenerator is prepared according to the method for preparing a negative electrode friction material for a friction nanogenerator according to any one of claims 1 to 7.

9. A friction nanogenerator, characterized in that: It comprises a stacked negative electrode, a negative electrode friction material and a positive electrode, wherein the negative electrode friction material is the negative electrode friction material for a friction nanogenerator according to claim 7, and the side of the negative electrode friction material having a micro-nano structure faces the positive electrode.

10. An application of the triboelectric nanogenerator according to claim 9, characterized in that: The friction nanogenerator is used for metal corrosion protection.

Citation Information

Patent Citations

  • Preparation method for polydimethylsiloxane film, polydimethylsiloxane film prepared through method and application of polydimethylsiloxane film

    CN106903831A

  • PDMS@F-MOF composite film for friction nanometer generator and preparation method for PDMS@F-MOF composite film

    CN111087635A